Pengaruh Motivasi dan Disiplin Kerja Terhadap Kinerja Karyawan - Novia Rahmawati (Digital Economic, Management and Accounting Knowledge Development (DEMAnD), 2020)
The research was conducted to prove that work motivation and discipline have an influence on the performance of employees of PT. Tiara Sarana Lestari Sukabumi City. The population taken is all employees at PT Tiara Sarana Lestari Sukabumi City, totaling 102 employees with a sample technique using 10% slovin, namely as many as 50 people. According to the purpose of the associative method used by researchers. The analysis technique uses multivariate regression, while the results, both partially and simultaneously, work motivation and discipline prove to have an extraordinary influence on employee performance at PT Tiara Sarana Lestari, Sukabumi City.